The Relationship of Objectively Measured Physical Activity and Sedentary Behaviour with Gestational Weight Gain and Birth Weight - Anneloes E. Ruifrok; Ellen Althuizen; Nicolette Oostdam; Willem van Mechelen; Ben Willem Mol; Christianne J. M. de Groot; Mireille N. M. van Poppel (Hindawi Limited, 2014)
Objective. To evaluate the relationship of physical activity (PA) and sedentary behaviour with gestational weight gain (GWG) and birth weight. Design. Combined data from two prospective studies: (1) nulliparous pregnant women without BMI restrictions and (2) overweight and obese pregnant women at risk for gestational diabetes. Methods. Daily PA and sedentary behaviour were measured with an accelerometer around 15 and at 32-35 weeks of gestation. The association between time spent in moderate-to-vigorous PA (MVPA) and in sedentary activities with GWG and birth weight was determined. Main outcome measures were GWG between 15 and 32 weeks of gestation, average GWG per week, and birth weight. Results. We studied 111 women. Early in pregnancy, 32% of women spent ≥30 minutes/day in at least moderate PA versus 12% in late pregnancy. No significant associations were found between time spent in MVPA or sedentary behaviour with GWG or birth weight. Conclusions. We found no relation between MVPA and sedentary behaviour with GWG or birth weight. The small percentage of women meeting the recommended levels of PA indicates the need to inform and support pregnant women to maintain regular PA, as there seems to be no adverse effect on birth weight and maintaining PA increases overall health.